Medical language – a unique linguistic phenomenon - Džuganová, Božena (Array, 2019)
Medical language is the language used by medical experts in their professional communication and incorporates more than 2,500 years of a development influenced mostly by Greek and Latin medical traditions. Its specific features and characteristics are studied from various aspects. It is closely connected with the immense development of technology and science that brings new concepts to the language; medical vocabulary is an open and continually changing phenomenon and its units often acquire new meanings. Learning English medical language that has become a lingua franca during the last few decades creates certain obstacles for learners in the form of collocations, irregular forms, existence of synonyms, doublets, abbreviations, false friends, etc. To manage medical language at an appropriate level requires looking for the most convenient teaching and learning strategies. Good proficiency of English medical language opens new horizons to medical professionals and offers various options of its application in practice. As an international means of communication it slowly penetrates into national medical vocabularies worldwide.